COVID‐19 partial school closures and mental health problems: A cross‐sectional survey of 11, 000 adolescents to determine those most at risk. Issue 2 (20th July 2021) - Mansfield, Karen L.; Newby, Danielle; Soneson, Emma; Vaci, Nemanja; Jindra, Christoph; Geulayov, Galit; Gallacher, John; Fazel, Mina
Abstract: Background: Understanding adolescents' mental health during lockdown and identifying those most at risk is an urgent public health challenge. This study surveyed school pupils across Southern England during the first COVID‐19 school lockdown to investigate situational factors associated with mental health difficulties and how they relate to pupils' access to in‐school educational provision. Methods: A total of 11, 765 pupils in years 8–13 completed a survey in June–July 2020, including questions on mental health, risk indicators and access to school provision. Pupils at home were compared to those accessing in‐school provision on risk and contextual factors and mental health outcomes. Multilevel logistic regression analyses compared the effect of eight risk and contextual factors, including access to in‐school provision, on depression, anxiety and self‐reported deterioration in mental wellbeing. Results: Females, pupils who had experienced food poverty and those who had previously accessed mental health support were at greatest risk of depression, anxiety and a deterioration in wellbeing. Pupils whose parents were going out to work and those preparing for national examinations in the subsequent school year were also at increased risk. Pupils accessing in‐school provision had poorer mental health, but this was accounted for by the background risk and contextual factors assessed, in line with the allocation of in‐school places to more vulnerable pupils. Conclusions: Although the strongest associations with poor mental health during school closures were established risk factors, further contextual factors of particular relevance during lockdown had negative impacts on wellbeing. Identifying those pupils at greatest risk for poor outcomes is critical for ensuring that appropriate educational and social support can be given to pupils either at home or in‐school during subsequent lockdowns. Abstract : This study assessed mental health and change in wellbeing in a large, diverse sample of pupils during the first UK COVID‐19 school closures, comparing pupils who remained at home with those who were accessing in‐school provision, and adjusting for situational factors. Pupils accessing in‐school provision had poorer mental health, but this was accounted for by pre‐existing vulnerability and contextual factors. Pupils most likely to report deteriorations in wellbeing were female, reported socio‐economic deprivation, had previous mental health needs or upcoming examinations.